Comparison of Color Uptake Effectiveness Between Disclosing Agent Tablets Derived from Mangosteen (Garcinia mangostana L.) Peel Extract and Its Fractions on Dental Plaque - Indah Muslimah; Adisty Restu Poetri; Andina Rizkia Putri Kusuma; Ade Ismail Abdul Kodir (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Plaque is a transparent layer that requires a coloring agent in the form of a disclosing agent to visualize it. Erythrosine, as one of the frequently used disclosing agents, has potential toxic side effects if used in the long term. Therefore, this study aims to compare the effectiveness of color absorption between tablets based on extracts and fractions of mangosteen fruit peel (Garcinia mangostana L.) with erythrosine as a control. Materials and Methods: This study employed a laboratory experimental design with a post-test-only controlled group design. A total of 36 healthy dental samples were divided into 9 groups, which were soaked in saliva for 8, 24, and 48 hours. After plaque formation, tablets of extracts, mangosteen peel fractions, and erythrosine were applied to the teeth. Results and Discussion: The results of analysis using the One-way ANOVA test showed that erythrosine tablets had significantly higher color absorption than the extract and mangosteen peel fraction tablets. Conclusion: Erythrosine is still a more effective option in highlighting dental plaque, but mangosteen peel-based tablets can be a safer natural alternative with potential for further development. Further research is recommended to optimize the formulation of mangosteen peel tablets to improve their effectiveness and convenience in clinical applications.